A framework for sustainable supply chain in emerging economies. Issue 3 (8th April 2019) - Queiroz, Maciel M.
Abstract: Sustainable supply chains (SSC) are an essential topic in emerging economies for achieving sustainable development. Because of their rapid economic growth, emerging economies are experiencing both sides of this development: the well‐being enhancement and the environmental impact. However, decision makers and practitioners do not have robust models for managing supply networks that consider the sustainability complexities. This study aims to provide a better understanding of SSC in emerging economies and proposes a generic framework to improve the decision‐making process. Based on a review of the literature, a decision framework for sustainability is proposed. A green sustainable decision concept is also discussed in the SSC literature. This study has implications for scholars, decision makers, and practitioners interested in advancing the SSC field based on an extension of the framework.